1999
DOI: 10.1007/pl00007363
|View full text |Cite
|
Sign up to set email alerts
|

Die Bedeutung der körperlichen Aktivität für die physiologische Streßreaktion

Abstract: The extent of physical activity and the dynamic performance capacity show an inverse relationship to cardiovascular mortality, independent of the influence of other risk factors, but the underlying mechanism remains uncertain. Most concepts assume that the aerobic capacity of the peripheral musculature is increased by training, and thus improved cardiocirculatory regulation and especially a more favorable stress reaction pattern are attained. This adaptation is essentially an inverse adaptation mechanism as in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…In this context, even wider LoA were found when comparing results from VThigh and several different LThigh determination methods [72]. Furthermore, the complex interaction of various methodologies in nonlinear HRV analysis with different recording devices and artefact correction methods [43,94,104] might influence the accuracy of the threshold determination. Based on the above-mentioned issues and gaps in the literature, HRVThigh concepts utilizing a nonlinear analysis of HRV need a further evaluation to ensure that they can be accurately and reliably applied in a larger number of individuals, including female participants.…”
Section: Hrvthigh Versus Lthighmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, even wider LoA were found when comparing results from VThigh and several different LThigh determination methods [72]. Furthermore, the complex interaction of various methodologies in nonlinear HRV analysis with different recording devices and artefact correction methods [43,94,104] might influence the accuracy of the threshold determination. Based on the above-mentioned issues and gaps in the literature, HRVThigh concepts utilizing a nonlinear analysis of HRV need a further evaluation to ensure that they can be accurately and reliably applied in a larger number of individuals, including female participants.…”
Section: Hrvthigh Versus Lthighmentioning
confidence: 99%
“…From the six studies that compared HRVTlow against LTlow four used time-domain based approaches [35,41,91,92], one used a time-frequency approach [93], and one used a nonlinear methodology [56], while the reference methods used for LTlow utilized three times the first increase from baseline, as well as baseline plus 0.2 mmol/l blood lactate concentration, Dickhuth-method [94] and 2 mmol/l blood lactate concentration, once each. The agreement between running speed at HRVTlow and LTlow was assessed in two studies and showed a moderate bias but relatively wide LoA (see Table 4).…”
Section: Hrvtlow Versus Ltlowmentioning
confidence: 99%
See 1 more Smart Citation
“…Mit dem Anstieg des Lactats über die aerobe Schwelle kommt es zu einem Anstieg der Plasmakatecholamine Adrenalin und Noradrenalin [9,29]. Der Anstieg geht parallel zur Lactatleistungskurve und erfolgt deshalb nach der aeroben Schwelle annähernd exponentiell [8,29].…”
Section: Aerobe Schwelleunclassified